HUBUNGAN PERAN KEPALA MADRASAH SEBAGAI MANAJER DENGAN KINERJA GURU - Muh. Hasbi; Ismail Nasar; Yinarti Hida; Ritmon Amala (Irfani (e-Journal), 2023)
The purpose of this study was to see the relationship between the principal as a manager and the performance of teachers in the Madrasah Aliyah Negeri Gorontalo District. In research that uses this type of quantitative research, the population is a saturated sample, with the number studied 32 people. The data analysis technique used a questionnaire, and the data analysis technique used was moment data analysis. Based on the research results, there is a positive/significant relationship between the role of the head of the madrasah as a manager and the performance of teachers in Madrasah Aliyah Negeri Gorontalo District. This is indicated by the results of calculating the performance coefficient between the teacher performance score (variable Y) and the role of the madrasah principal as manager (variable X), which was obtained at 32.15%. This shows that the principal as a manager and teacher performance has a strong enough relationship, namely: 0.567 and positive, which means that the relationship between the head of the madrasah and a manager increases, so the teacher's performance will also increase.